Biography and social exclusion in Europe experiences and life journeys - Chamberlayne, Prue ca. 20./21. Jh; Wengraf, Tom 1939-; Rustin, Michael 1938- (Policy Press, 2002)
Throughout Europe, standardised approaches to social policy and practice are being radically questioned and modified. Beginning from the narrative detail of individual lives, this book re-thinks welfare predicaments, emphasising gender, generation, ethnic and class implications of economic and social deregulation
Title from publisher's bibliographic system (viewed on 20 Jan 2022)
Keywords: Marginality, Social / European Union countries / Case studies; Social sciences / Biographical methods; Social control / European Union countries; European Union countries / Social policy